2020
DOI: 10.1098/rsos.200837
|View full text |Cite
|
Sign up to set email alerts
|

Integrative taxonomy revisits the ontogeny and trophic niches ofRimicarisvent shrimps

Abstract: Among hydrothermal vent species, Rimicaris exoculata is one of the most emblematic, hosting abundant and diverse ectosymbioses that provide most of its nutrition. Rimicaris exoculata co-occurs in dense aggregates with the much less abundant Rimicaris chacei in many Mid-Atlantic Ridge vent fields. This second shrimp also houses ectosymbiotic microorganisms but has a mixotrophic diet. Recent observations have suggested potential misidentific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(68 citation statements)
references
References 54 publications
5
63
0
Order By: Relevance
“…Among the 519 juveniles examined from the July 1997 expedition, Shank et al (1998) found no males and suggested that: (1) male sexual characteristics were not displayed by juveniles, or (2) R. exoculata could be a protogynous hermaphrodite. Komai & Segonzac (2008) reported that the smallest male they determined by the pleopod morphology was 10.1 mm in carapace length, corresponding to their stage D, or subadults (stage C-subadults for Methou et al 2020), corroborating the first hypothesis of Shank et al (1998).…”
Section: Juvenilessupporting
confidence: 59%
See 4 more Smart Citations
“…Among the 519 juveniles examined from the July 1997 expedition, Shank et al (1998) found no males and suggested that: (1) male sexual characteristics were not displayed by juveniles, or (2) R. exoculata could be a protogynous hermaphrodite. Komai & Segonzac (2008) reported that the smallest male they determined by the pleopod morphology was 10.1 mm in carapace length, corresponding to their stage D, or subadults (stage C-subadults for Methou et al 2020), corroborating the first hypothesis of Shank et al (1998).…”
Section: Juvenilessupporting
confidence: 59%
“…Vereshchaka (1997) indicated a settling stage between 3 and 5 mm in carapace length. The smallest stage A juvenile collected, close to adults, by Methou et al (2020) was 5.7 mm in carapace length.…”
Section: Settlementmentioning
confidence: 94%
See 3 more Smart Citations